2009
DOI: 10.1590/s0103-50532009000600008
|View full text |Cite
|
Sign up to set email alerts
|

Potential application in biocatalysis of mycelium-bound lipases from Amazonian fungi

Abstract: Neste trabalho foram avaliados 212 fungos isolados de plantas da Região Amazônica quanto ao potencial de aplicação em biocatálise como fornecedores de lipases ligadas ao micélio. Estes isolados foram submetidos a ensaios de atividade hidrolítica e sintética. Quando submetidos ao ensaio com o substrato tributirina, 87% dos isolados apresentaram atividade hidrolítica. Destes, 30% mostraram bom crescimento em meio líquido indutor de lipase, e foram submetidos à avaliação sintética em reações de esterificação e tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Dichloromethane was dried over CaH 2 and distilled immediately before use. 1 H NMR (300.01 MHz, CDCl 3 ) and 13 C NMR (75.50 MHz, CDCl 3 ) spectra were recorded on a Gemini 300P from Varian Instruments using (CH 3 ) 4 Si as internal reference (d 0.00). Chemical shifts d are given in ppm and coupling constants J are given in hertz.…”
Section: General Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dichloromethane was dried over CaH 2 and distilled immediately before use. 1 H NMR (300.01 MHz, CDCl 3 ) and 13 C NMR (75.50 MHz, CDCl 3 ) spectra were recorded on a Gemini 300P from Varian Instruments using (CH 3 ) 4 Si as internal reference (d 0.00). Chemical shifts d are given in ppm and coupling constants J are given in hertz.…”
Section: General Methodsmentioning
confidence: 99%
“…The immense Brazilian biodiversity especially from soil, that is a rich source of microorganisms, has motivated the search for new biocatalysts with special characteristics aiming at biotechnological applications. 1 These microorganisms can metabolize and biotransform regio-and enantioselectively an enormous range of natural and synthetic organic compounds using different enzymes. 2 Among these, the hydrolases (E.C.…”
Section: Introductionmentioning
confidence: 99%
“…Recentemente, Zanotto et al, 85 isolaram fungos de plantas da Região Amazônica, Brasil, os quais foram avaliados como fontes de lipase ligada ao micélio, visando aplicação em reações de biotransformação. Neste estudo, foram isolados um total de 212 fungos, sendo 77 fungos endofíticos, 45 fungos fitopatogênicos e 90 fungos degradadores de madeira, extraídos de fontes como sementes, frutas, hastes, folhas e raízes.…”
Section: Síntese De éSteresunclassified
“…They reported the most promising fungi with hydrolytic activity against tributyrin belonged to Penicillium and Aspergillus genera. It is worth mentioning Zanotto et al (2009) pointed out triacylglycerols such as triolein or tributyrin are suitable substrates for the determination of lipase and esterase activity, respectively. Wolski et al (2009) reported the partial characterization of enzymatic extracts produced by a newly isolated Penicillium sp.…”
Section: New Sources Of Lipasesmentioning
confidence: 99%
“…In the solid state fermentation, soybean bran was used as a low-cost substrate. Zanotto et al (2009) were able to isolate three fungi from plants of the Amazon region with a great potential as providers of mycelium-bound lipases for use in biotransformations (good hydrolysis activity, and good esterification and transesterification capacity in organic media). Chen et al (2009) attained 91.08% of fatty acid methyl esters in the alcoholysis of an waste cooking oil catalyzed by the lipase derived from Candida sp.…”
Section: New Sources Of Lipasesmentioning
confidence: 99%